Object analysis and species identification of an Asháninka hood from the Rio Ene valley, Peru - Fernandes Caromano, Caroline; Kaki, Walid Dani; Van Andel, Tinde; Kockelkorn, Max (Ethnobiology and Conservation, 2024)
A cotton headdress ornamented with several botanical and faunal elements (TM-5074-2) is kept in the depot of the Wereldmuseum in Amsterdam. There is little information about the provenance of the object or its context of use. Identified by the museum as a ‘shaman hood’, is said to have been obtained from an Asháninka indigenous community along the Ene River, Peruvian Amazon. The unusual composition of the hood, with 16 bundles of bird fragments, 39 bundles of mammal parts, and 3332 seeds, raises several questions. Is the object a traditional Asháninka ornament? Is the combination of so many distinct elements a result of later additions? Is it possible that the hood was manufactured for sale? In addition to literature research, the identification of the biological material can offer some clues if the object was manufactured in the same region inhabited by the Asháninka communities. Through the morphological comparison of the plant and animal parts attached to the hood with the botanical and zoological collections of the Naturalis Biodiversity Center, this study aimed to provide new tools for provenance research, by identifying the species present in the object. As a result, eight different plant species, eight bird taxa and at least eight mammal taxa attached to the object were identified, most of them native to the Peruvian Amazon. Finally, with the identification of the species, we proposed possible interpretations for the selection of plants and animals added to the shaman hood based on the historical context and the Asháninka worldview.